Broadband and High-Efficiency Excitation of Spoof Surface Plasmon Polaritons Through Rectangular Waveguide - Tang, Wenxuan; Wang, Jiangpeng; Yan, Xiaotian; Liu, Junfeng; Gao, Xinxin; Zhang, Lepeng; Cui, Tie Jun (Frontiers in Physics, 2020)
Spoof surface plasmon polaritons (SPPs) are highly localized surface waves that can be supported on metal surfaces with subwavelength decorations. Mode matching and momentum matching have been investigated so as to efficiently excite the spoof SPPs through conventional planar waveguides (WGs) such as the microstrip (MS) line and the co-planar waveguide (CPW). In this work, a smooth and wideband bridge between the conventional rectangular waveguide and the plasmonic waveguide of spoof SPPs has been proposed and experimentally demonstrated. High efficiency is achieved in both simulation and experiment in a wide frequency range from 12 to 18 GHz. The high-efficiency and broadband excitation of spoof SPPs through rectangular waveguide has great potentials in microwave, millimeter-wave and terahertz circuits and systems.